Implementasi Sistem Pakar Diagnosa Penyakit Ayam Pedaging Pada Peternakan PT. Cemerlang Unggas Lestari - Kurriana Putra, Iqbal (Najah: Journal of Research and Community Service, 2024)
At PT. Cemerlang Unggas Lestari, the mass death of 12,563 chickens over the past two years has negatively impacted company revenue, primarily due to disease outbreaks and declining poultry health. The limited knowledge of farmers about poultry diseases has exacerbated the situation. As a solution, the development of an expert system using the FK-NN (Fuzzy K-Nearest Neighbors) method can assist in diagnosing diseases and providing treatment guidance. This system operates by inputting observed symptoms to identify potential diseases. Testing 12 diseases and 42 symptoms using a dataset from the Central Java Livestock and Animal Health Department. This expert system is expected to reduce chicken mortality, enhance farmers' knowledge, and improve operational efficiency in poultry farming.